2021
DOI: 10.3390/ijms22189957
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Analyses of Drought/Salt-Responsive Cytochrome P450 Genes in Medicago truncatula

Abstract: Cytochrome P450 monooxygenases (P450s) catalyze a great number of biochemical reactions and play vital roles in plant growth, development and secondary metabolism. As yet, the genome-scale investigation on P450s is still lacking in the model legume Medicago truncatula. In particular, whether and how many MtP450s are involved in drought and salt stresses for Medicago growth, development and yield remain unclear. In this study, a total of 346 MtP450 genes were identified and classified into 10 clans containing 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 78 publications
(93 reference statements)
0
13
0
Order By: Relevance
“…On the other hand, the two other genes, HORVU7Hr1G101590 and HORVU7Hr1G103510 encode Cytochrome P450 superfamily protein and transducin/WD40 repeat-like superfamily protein (WD40), respectively. Both of these gene products participate in response to salt stress ( Mao et al., 2013 , Sun Z et al., 2018 , Sun et al., 2021 ; Xia et al., 2021 ; Xin et al., 2021 ). However, the detailed function of these genes concerning salt tolerance in barley remains to be investigated by gene-editing and gain-of-function-based genetic engineering.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the two other genes, HORVU7Hr1G101590 and HORVU7Hr1G103510 encode Cytochrome P450 superfamily protein and transducin/WD40 repeat-like superfamily protein (WD40), respectively. Both of these gene products participate in response to salt stress ( Mao et al., 2013 , Sun Z et al., 2018 , Sun et al., 2021 ; Xia et al., 2021 ; Xin et al., 2021 ). However, the detailed function of these genes concerning salt tolerance in barley remains to be investigated by gene-editing and gain-of-function-based genetic engineering.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a total of 687 BnCYP450 genes were identified from Brassica napus cultivar ZS11, which is assigned into 22 subfamilies and clustered into nine clans ( Table 1 ). The number of BnCYP450s was greater than those of Arabidopsis (251), Brassica rapa (354), Brassica oleracea (343), rice (355), apple (348), tomato (457), cotton (461), model legume (346), grape (236), and fewer than in wheat (1700) [ 22 , 23 , 24 , 25 , 27 , 28 ]. Some subfamilies and clans showed deep phylogenetic relationships.…”
Section: Discussionmentioning
confidence: 99%
“…The CYP450s catalyze a great number of NADPH- and/or O 2 -dependent oxygenation/hydroxylation reactions in many organisms [ 21 , 23 ]. The CYP450 genes are widely identified in most organisms, including bacteria, plants, animals, and humans [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. In plants, the nomenclature of CYP450 genes is generally classified into two groups: A type and non-A type [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the NF-YB subfamily plays key role in improving drought tolerance in plants such as Arabidopsis [13], tobacco [18], and maize [19]. Gene families such as P450 [23], HD-ZIP [24], SRS [25], and PcG [26] in Medicago have been identified. These families are related to abiotic stress and growth, but the NF-YB gene family has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%